Cell alignment on novel polymeric micro-hollow fiber membranes for neural and musculoskeletal tissue engineering - Scott J. Allan; David R. Jenkins; Anna Osborne; Rachael Wood; Georgios Mikalef; Cinzia Amieni; Luca Adly Megalaa Shokralla; Zoe Schofield; Ivan Wall; Eric Hill; Marianne J. Ellis; Patricia Perez Esteban (Cell and Tissue Research, 2026)
Precise positioning and alignment of specific cell types, such as those in the central nervous system and the muscular system, is essential for their functional integration, their migration, and proliferation in vivo. Cell alignment in physiologically relevant tissue models and constructs is challenging to reproduce in vitro unless a three-dimensional scaffold is used. This study demonstrates that cell alignment can be guided quickly, inexpensively, and efficiently using polymeric micro-hollow fiber membranes. These micro-hollow fiber membranes are fabricated via single orifice wet spinning from biocompatible polymers—polystyrene and polycaprolactone. The physicochemical characterization of the micro-hollow fiber membranes confirmed their unique architecture, presenting a special patterning on their outer surface. To establish their potential as a platform for cell alignment via contact guidance, the viability, and degree of alignment of relevant cell lines were evaluated when cultured on the micro-hollow fiber membranes. NG108-15, olfactory ensheathing cells and SH-SY5Y cells were used with the aim to simulate the microspatial distribution of cells within the spinal cord, and C2C12 myoblasts were selected to mimic the highly organized structure seen in muscle tissue. Moreover, differentiation of SH-SY5Y cells was successfully induced while cells remained aligned with respect to the micro-HFM’s axis. The degree of alignment in all cases was quantified via image analysis in combination with the Fast Fourier Transform algorithm method. This work establishes a platform with very particular micro-topographical features that can be employed to direct growth, orientation, and even differentiation of various cell types for tissue engineering and in vitro modelling.

Multidecadal increase in microbial biomass and production along the western Antarctic Peninsula - Hugh W. Ducklow; Oscar M. Schofield; Sharon E. Stammerjohn; David L. Kirchman (Deep Sea Research Part I: Oceanographic Research Papers, 2026)

Vulnerability of marine megafauna to global at‐sea anthropogenic threats - Michelle VanCompernolle; Juliet Morris; Hannah J. Calich; Jorge P. Rodríguez; Sarah A. Marley; Jessica R. Pearce; Briana Abrahms; Katya Abrantes; André S. Afonso; Alex Aguilar; Andrews Agyekumhene; Tomonari Akamatsu; et al. (Conservation Biology, 2026)
Marine megafauna species are affected by a wide range of anthropogenic threats. To evaluate the risk of such threats, species’ vulnerability to each threat must first be determined. We build on the existing threats classification scheme and ranking system of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species by assessing the vulnerability of 256 marine megafauna species to 23 at‐sea threats. The threats we considered included individual fishing gear types, climate‐change‐related subthreats not previously assessed, and threats associated with coastal impacts and maritime disturbances. Our ratings resulted in 70 species having high vulnerability ( v > 0.778 out of 1) to at least 1 threat, primarily drifting longlines, temperature extremes, or fixed gear. These 3 threats were also considered to have the most severe effects (i.e., steepest population declines). Overall, temperature extremes and plastics and other solid waste were rated as affecting the largest proportion of populations. Penguins, pinnipeds, and polar bears had the highest vulnerability to temperature extremes. Bony fishes had the highest vulnerability to drifting longlines and plastics and other solid waste; pelagic cetaceans to 4 maritime disturbance threats; elasmobranchs to 5 fishing threats; and flying birds to drifting longlines and 2 maritime disturbance threats. Sirenians and turtles had the highest vulnerability to at least one threat from all 4 categories. Despite not necessarily having severe effects for most taxonomic groups, temperature extremes were rated among the top threats for all taxa except bony fishes. The vulnerability scores we provide are an important first step in estimating the risk of threats to marine megafauna. Importantly, they help differentiate scope from severity, which is key to identifying threats that should be prioritized for mitigation.

Influence of traffic volume on mammal beta diversity within the road effect zone - Thomas J. Yamashita; David B. Wester; Zachary M. Wardle; Daniel G. Scognamillo; Landon R. Schofield; Michael E. Tewes; John H. Young; Jason V. Lombardi (Biological Conservation, 2025)

Mars thermal inertia and surface temperatures by the Mars Climate Sounder - Sylvain Piqueux; David M. Kass; Armin Kleinböhl; Marek Slipski; Paul O. Hayne; Daniel J. McCleese; John T. Schofield; Nicholas Heavens (Icarus, 2024)

The contamination of in situ archaeological remains: A pilot analysis of microplastics in sediment samples using μFTIR - Jeanette M. Rotchell; Freija Mendrik; Emma Chapman; Paul Flintoft; Ian Panter; Giulia Gallio; Christine McDonnell; Catriona R. Liddle; David Jennings; John Schofield (Science of The Total Environment, 2024)

Priorities for Mediterranean marine turtle conservation and management in the face of climate change - Antonios D. Mazaris; Charalampos Dimitriadis; Maria Papazekou; Gail Schofield; Aggeliki Doxa; Anastasia Chatzimentor; Oguz Turkozan; Stelios Katsanevakis; Aphrodite Lioliou; Sara Abalo-Morla; Mustapha Aksissou; Antonella Arcangeli; et al. (Journal of Environmental Management, 2023)

A surplus no more? Variation in krill availability impacts reproductive rates of Antarctic baleen whales - Logan J. Pallin; Nick M. Kellar; Debbie Steel; Natalia Botero‐Acosta; C. Scott Baker; Jack A. Conroy; Daniel P. Costa; Chris M. Johnson; David W. Johnston; Ross C. Nichols; Doug P. Nowacek; Andrew J. Read; et al. (Global Change Biology, 2023)
The krill surplus hypothesis of unlimited prey resources available for Antarctic predators due to commercial whaling in the 20th century has remained largely untested since the 1970s. Rapid warming of the Western Antarctic Peninsula (WAP) over the past 50 years has resulted in decreased seasonal ice cover and a reduction of krill. The latter is being exacerbated by a commercial krill fishery in the region. Despite this, humpback whale populations have increased but may be at a threshold for growth based on these human‐induced changes. Understanding how climate‐mediated variation in prey availability influences humpback whale population dynamics is critical for focused management and conservation actions. Using an 8‐year dataset (2013–2020), we show that inter‐annual humpback whale pregnancy rates, as determined from skin‐blubber biopsy samples ( n = 616), are positively correlated with krill availability and fluctuations in ice cover in the previous year. Pregnancy rates showed significant inter‐annual variability, between 29% and 86%. Our results indicate that krill availability is in fact limiting and affecting reproductive rates, in contrast to the krill surplus hypothesis. This suggests that this population of humpback whales may be at a threshold for population growth due to prey limitations. As a result, continued warming and increased fishing along the WAP, which continue to reduce krill stocks, will likely impact this humpback whale population and other krill predators in the region. Humpback whales are sentinel species of ecosystem health, and changes in pregnancy rates can provide quantifiable signals of the impact of environmental change at the population level. Our findings must be considered paramount in developing new and more restrictive conservation and management plans for the Antarctic marine ecosystem and minimizing the negative impacts of human activities in the region.

Agricultural systems regulate plant and insect diversity and induce ecosystem novelty - Jessie Woodbridge; Ralph Fyfe; David Smith; Anne de Varielles; Ruth Pelling; Michael J. Grant; Robert Batchelor; Robert Scaife; James Greig; Petra Dark; Denise Druce; Geoff Garbett; et al. (Anthropocene, 2023)

High polygenic risk score for exceptional longevity is associated with a healthy metabolic profile - Mary Revelas; Anbupalam Thalamuthu; Anna Zettergren; Christopher Oldmeadow; Jenna Najar; Nazib M. Seidu; Nicola J. Armstrong; Carlos Riveros; John B. Kwok; Peter R. Schofield; Julian N. Trollor; Margda Waern; et al. (GeroScience, 2023)
Healthy metabolic measures in humans are associated with longevity. Dysregulation leads to metabolic syndrome (MetS) and negative health outcomes. Recent exceptional longevity (EL) genome wide association studies have facilitated estimation of an individual’s polygenic risk score (PRS) for EL. We tested the hypothesis that individuals with high ELPRS have a low prevalence of MetS. Participants were from five cohorts of middle-aged to older adults. The primary analyses were performed in the UK Biobank (UKBB) ( n = 407,800, 40–69 years). Replication analyses were undertaken using three Australian studies: Hunter Community Study ( n = 2122, 55–85 years), Older Australian Twins Study ( n = 539, 65–90 years) and Sydney Memory and Ageing Study ( n = 925, 70–90 years), as well as the Swedish Gothenburg H70 Birth Cohort Studies ( n = 2273, 70–93 years). MetS was defined using established criteria. Regressions and meta-analyses were performed with the ELPRS and MetS and its components. Generally, MetS prevalence (22–30%) was higher in the older cohorts. In the UKBB, high EL polygenic risk was associated with lower MetS prevalence (OR = 0.94, p = 1.84 × 10 –42 ) and its components ( p < 2.30 × 10 – 8 ). Meta-analyses of the replication cohorts showed nominal associations with MetS ( p = 0.028) and 3 MetS components ( p < 0.05). This work suggests individuals with a high polygenic risk for EL have a healthy metabolic profile promoting longevity.

A novel method for identifying coded tags recorded on aquatic acoustic monitoring systems - Christopher D. Lowe; Nicolas J. C. Tregenza; Claudia J. Allen; Georgina E. Blow; Hanna Nuuttila; Chiara M. Bertelli; Anouska F. Mendzil; Thomas Stamp; Emma V. Sheehan; Peter Davies; Jonathan C. D. Gordon; Jonathan D. Bolland; et al. (Environmental Monitoring and Assessment, 2022)
Aquatic biotelemetry increasingly relies on using acoustic transmitters (‘tags’) that enable passive detection of tagged animals using fixed or mobile receivers. Both tracking methods are resource-limited, restricting the spatial area in which movements of highly mobile animals can be measured using proprietary detection systems. Transmissions from tags are recorded by underwater noise monitoring systems designed for other purposes, such as cetacean monitoring devices, which have been widely deployed in the marine environment; however, no tools currently exist to decode these detections, and thus valuable additional information on animal movements may be missed. Here, we describe simple hybrid methods, with potentially wide application, for obtaining information from otherwise unused data sources. The methods were developed using data from moored, acoustic cetacean detectors (C-PODs) and towed passive receiver arrays, often deployed to monitor the vocalisations of cetaceans, but any similarly formatted data source could be used. The method was applied to decode tag detections that were found to have come from two highly mobile fish species, bass ( Dicentrarchus labrax ) and Twaite shad ( Alosa fallax ), that had been tagged in other studies. Decoding results were validated using test tags; range testing data were used to demonstrate the relative efficiency of these receiver methods in detecting tags. This approach broadens the range of equipment from which acoustic tag detections can be decoded. Novel detections derived from the method could add significant value to past and present tracking studies at little additional cost, by providing new insights into the movement of mobile animals at sea.

Comprehension of skin cancer genetic risk feedback in primary care patients - Erva Khan; Kimberly A. Kaphingst; Kirsten Meyer White; Andrew Sussman; Dolores Guest; Elizabeth Schofield; Yvonne T. Dailey; Erika Robers; Matthew R. Schwartz; Yuelin Li; David Buller; Keith Hunley; et al. (Journal of Community Genetics, 2022)

Identification and analysis of the bacterial endosymbiont specialized for production of the chemotherapeutic natural product ET ‐743 - Michael M. Schofield; Sunit Jain; Daphne Porat; Gregory J. Dick; David H. Sherman (Environmental Microbiology, 2015)
Summary Ecteinascidin 743 ( ET ‐743, Y ondelis) is a clinically approved chemotherapeutic natural product isolated from the Caribbean mangrove tunicate E cteinascidia turbinata . Researchers have long suspected that a microorganism may be the true producer of the anticancer drug, but its genome has remained elusive due to our inability to culture the bacterium in the laboratory using standard techniques. Here, we sequenced and assembled the complete genome of the ET ‐743 producer, C andidatus Endoecteinascidia frumentensis, directly from metagenomic DNA isolated from the tunicate. Analysis of the ∼631 kb microbial genome revealed strong evidence of an endosymbiotic lifestyle and extreme genome reduction. Phylogenetic analysis suggested that the producer of the anti‐cancer drug is taxonomically distinct from other sequenced microorganisms and could represent a new family of Gammaproteobacteria. The complete genome has also greatly expanded our understanding of ET ‐743 production and revealed new biosynthetic genes dispersed across more than 173 kb of the small genome. The gene cluster's architecture and its preservation demonstrate that the drug is likely essential to the interactions of the microorganism with its mangrove tunicate host. Taken together, these studies elucidate the lifestyle of a unique, and pharmaceutically important microorganism and highlight the wide diversity of bacteria capable of making potent natural products.

Highly depleted isotopic compositions evident in Iapetus and Rheic Ocean basalts: implications for crustal generation and preservation - J. Brendan Murphy; John W. F. Waldron; David I. Schofield; Tiffany L. Barry; Adrian R. Band (International Journal of Earth Sciences, 2014)

The ENIGMA Consortium: large-scale collaborative analyses of neuroimaging and genetic data - Paul M. Thompson; Jason L. Stein; Sarah E. Medland; Derrek P. Hibar; Alejandro Arias Vasquez; Miguel E. Renteria; Roberto Toro; Neda Jahanshad; Gunter Schumann; Barbara Franke; Margaret J. Wright; Nicholas G. Martin; et al. (Brain Imaging and Behavior, 2014)

A Longman's beaked whale ( Indopacetus pacificus ) strands in Maui, Hawaii, with first case of morbillivirus in the central Pacific - Kristi L. West; Susan Sanchez; David Rotstein; Kelly M. Robertson; Sophie Dennison; Gregg Levine; Nicole Davis; David Schofield; Charles W. Potter; Brenda Jensen (Marine Mammal Science, 2013)

Neuronal fiber bundle lengths in healthy adult carriers of the ApoE4 allele: A quantitative tractography DTI study - Lauren E. Salminen; Peter R. Schofield; Elizabeth M. Lane; Jodi M. Heaps; Kerrie D. Pierce; Ryan Cabeen; David H. Laidlaw; Erbil Akbudak; Thomas E. Conturo; Stephen Correia; Robert H. Paul (Brain Imaging and Behavior, 2013)

The mammalian gene function resource: the international knockout mouse consortium - Allan Bradley; Konstantinos Anastassiadis; Abdelkader Ayadi; James F. Battey; Cindy Bell; Marie-Christine Birling; Joanna Bottomley; Steve D. Brown; Antje Bürger; Carol J. Bult; Wendy Bushell; Francis S. Collins; et al. (Mammalian Genome, 2012)

Photosynthetic energy storage efficiency in Chlamydomonas reinhardtii, based on microsecond photoacoustics - Chengyi Yan; Oscar Schofield; Zvy Dubinsky; David Mauzerall; Paul G. Falkowski; Maxim Y. Gorbunov (Photosynthesis Research, 2011)

Diet of pygmy sperm whales ( Kogia breviceps ) in the Hawaiian Archipelago - Kristi L. West; William A. Walker; Robin W. Baird; Whitney White; Gregg Levine; Eric Brown; David Schofield (Marine Mammal Science, 2009)

Coastal Sediment Dynamics and River Discharge as Key Factors Influencing Coastal Ecosystem Productivity in Southeastern Lake Michigan - Steven Lohrenz; Gary Fahnenstiel; Oscar Schofield; David Millie (Oceanography, 2008)

Integration of Mouse Phenome Data Resources - John M. Hancock; Niels C. Adams; Vassilis Aidinis; Andrew Blake; Judith A. Blake; Molly Bogue; Steve D. M. Brown; Elissa J. Chesler; Duncan Davidson; Christopher Duran; Janan T. Eppig; Valérie Gailus-Durner; et al. (Mammalian Genome, 2008)

A DIVERGENT mtDNA LINEAGE AMONG MESOPLODON BEAKED WHALES: MOLECULAR EVIDENCE FOR A NEW SPECIES IN THE TROPICAL PACIFIC? - Merel L. Dalebout; C. Scott Baker; Debbie Steel; Kelly M. Robertson; Susan J. Chivers; William F. Perrin; James G. Mead; Roger V. Grace; T. David Schofield (Marine Mammal Science, 2007)

CASE STUDY: MORBIDITY IN A PYGMY SPERM WHALE KOGIA BREVICEPS DUE TO OCEAN‐BOURNE PLASTIC - M. Andrew Stamper; Brent R. Whitaker; T. David Schofield (Marine Mammal Science, 2006)

Physical-Biological Coupling in Southern Lake Michigan: Influence of Episodic Sediment Resuspension on Phytoplankton - David F. Millie; Gary L. Fahnenstiel; Steven E. Lohrenz; Hunter J. Carrick; Thomas H. Johengen; Oscar M.E. Schofield (Aquatic Ecology, 2003)

Tight Regulation and Modulation via a C1-Regulated Promoter in Escherichia coli and Pseudomonas aeruginosa - David A. Schofield; Caroline Westwater; Joseph W. Dolan; James S. Norris; Michael G. Schmidt (Current Microbiology, 2002)

Use of differential fluorescence induction and optical trapping to isolate environmentally induced genes - David Allaway; Neil A. Schofield; Mary E. Leonard; Liliana Gilardoni; Turlough M. Finan; Philip S. Poole (Environmental Microbiology, 2001)
The techniques of differential fluorescence induction (DFI) and optical trapping (OT) have been combined to allow the identification of environmentally induced genes in single bacterial cells. Designated DFI‐OT, this technique allows the in situ isolation of genes driving the expression of green fluorescent protein (Gfp) using temporal and spatial criteria. A series of plasmid‐based promoter probe vectors (pOT) was developed for the construction of random genomic libraries that are linked to gfpUV or egfp . Bacteria that do not express Gfp on laboratory medium (i.e. non‐fluorescent) were inoculated into the environment, and induced genes were detected with a combined fluorescence/optical trapping microscope. Using this selection strategy, rhizosphere‐induced genes with homology to thiamine pyrophosphorylase ( thiE ) and cyclic glucan synthase ( ndvB ) were isolated. Other genes were expressed late in the stationary phase or as a consequence of surface‐dependent growth, including fixND and metX , and a putative ABC transporter of putrescine. This strategy provides a unique ability to combine spatial, temporal and physical information to identify environmental regulation of bacterial gene expression.

Optical traps: shedding light on biological processes - David Allaway; Neil A. Schofield; Philip S. Poole (Biotechnology Letters, 2000)

Optical discrimination of a phytoplankton species in natural mixed populations - Gary J. Kirkpatrick; David F. Millie; Mark A. Moline; Oscar Schofield (Limnology and Oceanography, 2000)
Developing optical detection techniques for discriminating particular phytoplankon species in mixed assemblages has long been a goal of aquatic scientists. Previously, a processing algorithm for phytoplankton absorption spectra was reported that suggested detection of the red tide dinoflagellate Gymnodinium breve was possible. The algorithm evaluated the fourth derivative of the particulate absorption spectrum of an unknown sample and compared it to a standard fourth derivative spectrum for G. breve using a similarity index. We report here the first‐time application of this technique to the detection of G. breve in natural, mixed phytoplankton communities. Pigment and spectral absorption data were collected from natural blooms of G. breve in the eastern Gulf of Mexico. This dinoflagellate is the only species of phytoplankton in the Eastern Gulf of Mexico observed to contain the pigment gyroxanthin‐diester, and it appears in constant proportion to cellular chlorophyll a (Chl a) in G. breve . The in vitro absorption spectrum of gyroxanthin‐diester is nearly identical to other xanthophylls (including diadinoxanthin, lutein, and 199‐hexanoyloxyfucoxanthin) and is not singularly responsible for imparting a unique absorption signature. Quantifying gyroxanthin‐diester and Chl a allowed us to estimate the fraction of the biomass in mixed populations associated with G. breve . Subsequent regression of the G. breve similarity indexes to the G. breve biomass fractions yielded a significant linear correlation. Finally, the liquid waveguide capillary cell appears to be a promising technology for automating this technique.

MONITORING A REHABILITATED HARBOR PORPOISE USING SATELLITE TELEMETRY - Andrew J. Westgate; Andrew J. Read; Tara M. Cox; T. David Schofield; Brent R. Whitaker; Kurt E. Anderson (Marine Mammal Science, 1998)

Detection of harmful algal blooms using photopigments and absorption signatures: A case study of the Florida red tide dinoflagellate, Gymnodinium breve - David F. Millie; Oscar M. Schofield; Gary J. Kirkpatrick; Geir Johnsen; Patricia A. Tester; Bryan T. Vinyard (Limnology and Oceanography, 1997)
The utility of photopigments and absorption signatures to detect and enumerate the red tide dinoflagellate, Gymnodinium breve, was evaluated in laboratory cultures and in natural assemblages. The carotenoid, gyroxanthindiester, was an adequate biomarker for G. breve biomass; water‐column concentrations corresponded with cell standing crops and chlorophyll a concentrations during bloom events in Sarasota Bay, Florida. Unlike other carotenoids, the relative abundance of gyroxanthin‐diester did not change throughout a range of physiological states in culture and the gyroxanthin‐diester: chlorophyll a ratio exhibited little variability in a natural assemblage during bloom senescence. Stepwise discriminant analysis indicated that wavelengths indicative of in vivo absorption by accessory chlorophylls and carotenoids could correctly discern spectra of the fucoxanthin‐containing G. breve from spectra of peridinin‐containing dinoflagellates, a diatom, a haptophyte, and a prasinophyte. With the use of a similarity algorithm, the increasing contribution of G. breve was discerned in absorption spectra (and corresponding fourth‐derivative plots) for hypothetical mixed assemblages. However, the absorption properties of chlorophyll c ‐containing algae vary little among taxa and it is difficult to discern the contribution of accessory chlorophylls and carotenoids caused by cell packaging. Therefore, the use of absorption spectra alone may not identify the contribution of a chlorophyll c ‐containing taxon to the composite spectrum of a mixed assemblage. This difficulty in distinguishing among spectra can be minimized by using the similarity algorithm in conjunction with fourth‐derivative analysis.